ANALISIS PENGETAHUAN DAN POLA MAKAN TERHADAP KEJADIAN HIPERTENSI PADA IBU HAMIL : Analysis of Knowledge and Eating Patterns on Incident of Hypertension in Pregnant Women - Syukma Ramadhani Faizal Nur; Silfia Angela Norce Halu; Maria Paula Marla Nahak; Prima Soultoni Akbar (Forind Press, 2023)
Hypertension in pregnancy can cause maternal morbidity or pregnancy including seizures or eclampsia, cerebral hemorrhage, pulmonary edema, acute kidney failure, and blood pooling and blood clotting in the blood vessels, as well as morbidity in the fetus, including delayed fetal growth in the womb, fetal death in the womb, placental abruption and premature birth. The aim of this research is to determine the effect of knowledge and diet on the incidence of hypertension in pregnant women. This was a quantitative study with a cross-sectional approach. The sampling technique used was total sampling, with a total of 32 respondents. The data was then analyzed using multiple linear regression analysis. The results of data analysis show that there is an influence of knowledge on the incidence of hypertension in pregnant women and it is statistically significant (b=-0.51, CI 95%= 0.25 - 0.72, p= <0.001). There is an influence of eating patterns on the incidence of hypertension in pregnant women and it is statistically significant (b=-0.54, CI 95%= 0.42 - 0.70), p= <0.001). Knowledge and eating patterns influence the incidence of hypertension in pregnant women.